Akuntansi Hijau: Penerapannya Pada Usaha Mikro Kecil Menengah Produksi Ikan - Rita, Rita; Farsiah, Lena; Noor, M. Arief; Saefullah, Aep; Amalia, Fisy Amalia; Darwanti, Dhenok; Lailani, Evi Okli; Djafri, Intan Arsitia (Penerbit Goodwood, 2025)
Purpose: This community service activity aims to introduce and enhance the understanding of green accounting among micro, small, and medium enterprises (MSMEs) in aquaculture, particularly fish farmers in Desa Cogreg, Kecamatan Parung, Bogor. The purpose is to increase accounting literacy, integrate environmental aspects into financial recording, promote cost efficiency, and raise awareness of business sustainability. Methodology/approach: The activity used a participatory–educative approach involving 25 fish farmers, with observation and interviews in the preparation stage, followed by counseling, discussions, and distribution of a simple FCR module. Evaluation focused on participants’ responses and their needs for further training and mentoring. Results/findings: The counseling increased participants’ understanding of green accounting. Although unfamiliar, they recognized existing eco-friendly practices—water reuse, feed efficiency, and sludge utilization—as recordable financial activities. Findings revealed a gap between ecological awareness and accounting documentation, emphasizing the need for recording formats Conclusions: The program found that green accounting in MSMEs remains at a pre-integration stage, with environmental awareness present but lacking systematic documentation. The activity improved initial literacy, though sustained mentoring and simple tools are still needed, and the study was limited by a small sample and short observation period. Limitations: This activity was limited by a small sample size, a single location, and a short observation period, which restricted the generalizability and long-term evaluation of the results. Contribution: This program links green accounting theory with MSME aquaculture practices, offering a community service model that supports sustainability and provides a replicable framework for similar future interventions.